If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3.4x + 5 = 22 Reorder the terms: 5 + 3.4x = 22 Solving 5 + 3.4x = 22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 3.4x = 22 + -5 Combine like terms: 5 + -5 = 0 0 + 3.4x = 22 + -5 3.4x = 22 + -5 Combine like terms: 22 + -5 = 17 3.4x = 17 Divide each side by '3.4'. x = 5 Simplifying x = 5
| 2.5x+2.5=12.5 | | 2.1(a+0.5)=-2.1(a+20) | | -5t-7t=2t | | -5x-24=2x+11 | | 5(c-1)-2(c+3)-2c=-8 | | 23=-3m+2 | | 11-4z=-27 | | 4y-14=6y-16 | | -5t-7t= | | -8x+4=3x+4 | | (x+16)+(7x-20)=180 | | .5x+4=.66x+.5 | | -3a+16=-20 | | 3x^2+27x-6= | | 8(2n+3)=9(4n+4)+2 | | -(6y+1)-(-5y-7)=-2 | | 17a-8=54-6y | | 4(2(10.5)+1)-3(2(10.5)-5)=40 | | 3t-66=899 | | -6+7x=-6-8x | | 4.9w+4.5=-1.1w-1.5 | | n-3n-4=18 | | 17=9*2y | | -18(n+13)=2(n-7) | | 5(x-1)=2.5 | | 4(5x-3)+39=-8(x-6)+14x-7 | | x^2-1=49 | | 41=7x-3+9 | | 5(x+5)=-6(2-2x)-7x | | 2x=-16-7 | | 7x+6=5x+20 | | 3x+6=x+12 |